First species of the family Bogidiellidae Hertzog, 1936 (Crustacea: Amphipoda) in Chilean groundwaters: Patagongidiella wefkoi n. sp. - Pérez-Schultheiss, Jorge (Zootaxa, 2013)
The first Chilean species of Bogidiellid amphipod, Patagongidiella wefkoi n. sp., is described from freshwater springs in the Osorno Province, Los Lagos Region. The new taxon is characterized principally by the structure of the hypertrophied facial robust seta present on the peduncle of male uropod 1, and the modified dimorphic setae on the exopod of male pleopod 2. The new species is described and illustrated and its morphological relationships with the other species of this group are discussed.